2012
DOI: 10.1016/j.nlm.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR by rapamycin in the amygdala or hippocampus impairs formation and reconsolidation of inhibitory avoidance memory

Abstract: Mammalian target of rapamycin (mTOR), a central regulator of protein synthesis in neurons, has been implicated in synaptic plasticity and memory. Here we show that mTOR inhibition by rapamycin in the basolateral amygdala (BLA) or dorsal hippocampus (DH) impairs both formation and reconsolidation of memory for inhibitory avoidance (IA) in rats. Male Wistar rats received bilateral infusions of vehicle or rapamycin into the BLA or DH before or after IA training or retrieval. Memory retention was tested at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 40 publications
5
65
2
Order By: Relevance
“…Furthermore, mTORC1 is implicated in synaptic function and memory (Costa-Mattioli et al, 2009;Kelleher et al, 2004). Previous behavioral studies showed that rapamycin treatment impaired LTM but not STM, which is consistent with the present findings, in which AMPK was found to be crucial for LTM formation but not STM (Jobim et al, 2012). In the present study, we also found that AMPK dephosphorylation in the CA1 after contextual fear conditioning was associated with an increase in p70s6k phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, mTORC1 is implicated in synaptic function and memory (Costa-Mattioli et al, 2009;Kelleher et al, 2004). Previous behavioral studies showed that rapamycin treatment impaired LTM but not STM, which is consistent with the present findings, in which AMPK was found to be crucial for LTM formation but not STM (Jobim et al, 2012). In the present study, we also found that AMPK dephosphorylation in the CA1 after contextual fear conditioning was associated with an increase in p70s6k phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…In adult brain mTORC1 regulates protein synthesis by activating p70 S6 kinase 1 and 2 (S6K1/2) and other unknown factors (Stoica et al 2011). Studies with the inhibitor rapamycin have established that mTORC1 is required for consolidation and reconsolidation of aversive LTM (Parsons et al 2006;Bekinschtein et al 2007;Stoica et al 2011;Jobim et al 2012). This is in agreement with an up-regulation of S6K1/2 phosphorylation 30-60 min after training (Parsons et al 2006;Bekinschtein et al 2007).…”
Section: Pi3kmentioning
confidence: 57%
“…3). Accordingly, pharmacological, functional imaging, and lesioning studies indicate an important role for the dorsal hippocampus in the reconsolidation of contextual fear conditioning (Boccia et al 2010;Jobim et al 2012;Lee et al 2013;De Jaeger et al 2014). These findings may also be interpreted as additional evidence supporting a role for hippocampal NMDA receptors, particularly those containing the GluN2 subunit, in memory reconsolidation (Pedreira et al 2002;Lee et al 2006;Ribeiro et al 2013), as far as the agonist and the antagonist of the polyaminebinding site at the NMDAr improved and disrupted memory reconsolidation, respectively.…”
Section: Discussionmentioning
confidence: 80%